Skeletal muscle stem cells modulate niche function in Duchenne muscular dystrophy mouse through YY1-CCL5 axis - Yang Li; Chuhan Li; Qiang Sun; Xingyuan Liu; Fengyuan Chen; Yeelo Cheung; Yu Zhao; Ting Xie; Bénédicte Chazaud; Hao Sun; Huating Wang (Nature Communications)
Abstract Adult skeletal muscle stem cells (MuSCs) are indispensable for muscle regeneration and tightly regulated by macrophages (MPs) and fibro-adipogenic progenitors (FAPs) in their niche. Deregulated MuSC/MP/FAP interactions and the ensuing inflammation and fibrosis are hallmarks of dystrophic muscle. Here we demonstrate intrinsic deletion of transcription factor Yin Yang 1 (YY1) in MuSCs exacerbates dystrophic pathologies by altering composition and heterogeneity of MPs and FAPs. Further analysis reveals YY1 loss induces expression of immune genes in MuSCs, including C-C motif chemokine ligand 5 (Ccl5). Augmented CCL5 secretion promotes MP recruitment via CCL5/C-C chemokine receptor 5 (CCR5) crosstalk, which subsequently hinders FAP clearance through elevated Transforming growth factor-β1 (TGFβ1). Maraviroc-mediated pharmacological blockade of the CCL5/CCR5 axis effectively mitigates muscle dystrophy and improves muscle performance. Lastly, we demonstrate YY1 represses Ccl5 transcription by binding to its enhancer thus facilitating promoter-enhancer looping. Altogether, our study demonstrates the critical role of MuSCs in actively shaping their niche and provides novel insight into the therapeutic intervention of muscle dystrophy.